PENDIDIKAN INKLUS - Supitno, Reni; Widiyawati, Widiyawati; Jamiyah, Siti; Hadiyanto, Hadiyanto (JURNAL DARMA AGUNG, 2025)
Inclusive Education is an educational service that provides opportunities for all students who have disabilities and require special services to be able to participate in learning activities in one class without distinction and discrimination. Formally, the implementation of Inclusive Education in Indonesia has only been implemented in the last ten years, but naturally Inclusive Education in Indonesia has been running for a long time. The implementation of Inclusive Education in Indonesia is based on the philosophy of our country's motto, namely Bhineka Tunggal Ika, the social culture of the Indonesian nation that upholds existing diversity. The foundation of inclusive education is rooted in the principles of justice and equality, which are stated in the 1945 Constitution and Law Number 20 of 2003 concerning the National Education System. This shows the state's commitment to providing quality education for all children, regardless of their background or physical condition. Inclusive Education has several characteristics, including: accommodating all types of student differences, providing a friendly and supportive learning environment, and involving all children in the learning process without separating them based on special needs.